2023
DOI: 10.3390/antibiotics12010084
|View full text |Cite
|
Sign up to set email alerts
|

Hiding in Plain Sight: Characterization of Aeromonas Species Isolated from a Recreational Estuary Reveals the Carriage and Putative Dissemination of Resistance Genes

Abstract: Antimicrobial resistance (AMR) has become one of the greatest challenges worldwide, hampering the treatment of a plethora of infections. Indeed, the AMR crisis poses a threat to the achievement of the United Nations’ Sustainable Development Goals and, due to its multisectoral character, a holistic approach is needed to tackle this issue. Thus, the investigation of environments beyond the clinic is of utmost importance. Here, we investigated thirteen strains of antimicrobial-resistant Aeromonas isolated from an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Among the eight bla KPC ‐positive strains, seven were assigned to the genus Aeromonas , including A. hydrophila , Aeromonas caviae , and Aeromonas ichthiosmia and one was identified as E. bugandensis , which has been previously mentioned. Both genera have already been described as carriers of bla KPC , but this finding in plastic‐associated strains has not been published by the time of the drafting of this paper and raises attention to the fact that these particles could act as vectors for clinically relevant genes (Canellas et al, 2023; Matteoli et al, 2020). Additionally, the bla KPC ‐positive strains were further investigated for the phenotypical production of carbapenemases by modified Hodge test, revealing that seven out of the eight strains were able to produce these enzymes, namely A. hydrophila , A. caviae , and E. bugandensis .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the eight bla KPC ‐positive strains, seven were assigned to the genus Aeromonas , including A. hydrophila , Aeromonas caviae , and Aeromonas ichthiosmia and one was identified as E. bugandensis , which has been previously mentioned. Both genera have already been described as carriers of bla KPC , but this finding in plastic‐associated strains has not been published by the time of the drafting of this paper and raises attention to the fact that these particles could act as vectors for clinically relevant genes (Canellas et al, 2023; Matteoli et al, 2020). Additionally, the bla KPC ‐positive strains were further investigated for the phenotypical production of carbapenemases by modified Hodge test, revealing that seven out of the eight strains were able to produce these enzymes, namely A. hydrophila , A. caviae , and E. bugandensis .…”
Section: Resultsmentioning
confidence: 99%
“…Aeromonas spp. can be found in a wide range of habitats and can thrive even under adverse conditions, such as in highly polluted waters like Guanabara Bay (floating plastic collection site) (Canellas et al, 2023). Although some species are known human and animal pathogens and may act as amplifiers of genetic transfer, it is worth mentioning that this genus is also remarkable for its still little‐explored biotechnological potential (Canellas & Laport, 2022; Lamy et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the identified genera, Aeromonas spp. are ubiquitous bacteria primarily found in most water environments and have recently gained attention as an arsenal of AMR genes and mobile genetic elements in natural environments ( Usui et al, 2016 ; Fernandez-Bravo and Figueras, 2020 ; Gomes et al, 2021 ; Maehana et al, 2021 ; Canellas et al, 2023 ). Previous studies have reported a higher prevalence of diverse AMR genes and integron cassettes in Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported a higher prevalence of diverse AMR genes and integron cassettes in Aeromonas spp. isolates ( Fernandez-Bravo and Figueras, 2020 ; Canellas et al, 2023 ). Maehana et al isolated Aeromonas spp.…”
Section: Discussionmentioning
confidence: 99%